Sustainable refurbishment - Shah, Sunil, 1974- (Hoboken : Wiley-Blackwell, 2012)
This guide to green'retro-fitting' for facility mangers struggling to reduce their building's carbon footprint will help in the planning and management of a sustainable refurbishment program. The first part of the book provides the context, presenting the structure and linkage between the other chapters. The second part provides technical support, helping to determine the feasibility of good practices as part of the refurbishment. Finally, the third part reviews refurbishment from a sector perspective, with case studies and examples showcasing previous good practices and lessons learned.
Includes bibliographical references and index.
Keywords: Sustainable buildings -- Design and construction; Buildings -- Repair and reconstruction; Green technology